2019
DOI: 10.1016/j.clinre.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell-mediated splanchnic cholestatic inflammation

Abstract: Introduction: Splanchnic mast cells increase in chronic liver and in acute-on-chronic liver diseases. We administered Ketotifen, a mast cell stabilizer, and measured the mast cells in the splanchnic organs of cholestatic rats. Material and Methods: These groups were studied: sham-operated rats (S; n = 15), untreated microsurgical cholestasic rats (C; n = 20) and rats treated with Ketotifen: early (SK-e; n = 20 and CKe; n = 18), and late (SK-l; n = 15 and CK-l; n = 14). Results: The cholestatic rats showed syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…(26) Our group demonstrated that MCs infiltrate the liver following injury and perpetuate cholestatic damage (8,9,24) and that stabilization of MCs in cholestatic models results in amelioration of DR, inflammation, and hepatic fibrosis. (27) Aside from traditional receptors, MCs express a number of other receptors and binding sites, including FXRβ and ASBT. (19) Our current work demonstrates that MC-derived FXR/FGF signaling regulates biliary damage and hepatic fibrosis.…”
Section: Bile Ductmentioning
confidence: 99%
“…(26) Our group demonstrated that MCs infiltrate the liver following injury and perpetuate cholestatic damage (8,9,24) and that stabilization of MCs in cholestatic models results in amelioration of DR, inflammation, and hepatic fibrosis. (27) Aside from traditional receptors, MCs express a number of other receptors and binding sites, including FXRβ and ASBT. (19) Our current work demonstrates that MC-derived FXR/FGF signaling regulates biliary damage and hepatic fibrosis.…”
Section: Bile Ductmentioning
confidence: 99%
“…It was suggested that MCs migrate into the liver and are activated in patients with cholestasis. Aller et al [22] found that an increase in splanchnic mast cells aggravated the in ammatory response in cholestasis rats. In turn, inhibition of MC mediators decreases ductular reaction and liver brosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ketotifen, an MC stabilizer, increased hepatic mucosal MC presence in cholestatic rats while decreasing the MC population in the mesenteric lymphatic complex and levels of TGF‐β1 and VEGF. [ 37 ]…”
Section: Diseases Implicated By MC Presence/activationmentioning
confidence: 99%